PENGARUH KINERJA DRIVER DAN FASILITAS APLIKASI TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN (Studi Kasus Gojek Kota Malang) - Nikin Hardati, Ratna (FIA UB, 2021)
Gojek, an online transportation service provider, is a social-spirited company that is leading the revolution in the ojek transportation industry. Gojek partners with experienced ojek riders to be the main solution in shipping goods, ordering food delivery, shopping and traveling in a traffic jam. The purpose of this study is to explain the effect of: Driver Performance on Customer Satisfaction, Effect of Application Facilities on Customer Satisfaction and Effect of Driver Performance and Application Facilities on Loyalty through Customer Satisfaction. This research is a quantitative research. The research population is Gojek customers in Malang City. The number of samples used was determined by the Proportional Random Sampling technique. Data analysis using the path analysis method (Path Analysis). The results showed that there was a significant influence between the performance of the driver on customer satisfaction Gojek; There is a significant influence between facilitiesÂ on customer satisfaction Â Gojek; There is a significant influence between driver performance and facilities simultaneously on customer satisfaction) Gojek; There is a significant influence between driver performance on customer loyalty Gojek; The existence of insignificant influence between facilities on customer loyalty Gojek; There is a significant influence between satisfaction on customer loyalty Gojek; and the existence of significant influence between the effect of driver performance, facilities, and satisfaction simultaneously on Gojek customer loyalty.